The didactics of philosophy and of philosophizing in france (1989- 2012). documentary assessment or «state» or the issue - Gómez Mendoza, Miguel Ángel (Universidad Pedagógica y Tecnológica de Colombia, 2013)
The documentary assessment begins, in a first moment, with the definition of concepts such as didactics and disciplinary didactics and their application in the approaches in the didactics of Philosophy as an academic and scholar discipline in the school and pedagogical French tradition. In a second moment, it is showed a state of the researches carried out in the field of the didactics of philosophy and of philosophizing in a period ranging from twenty to twenty-five years in the «terminal» class –three last years of secondary school leading to «baccalauréat» title– in the high middle school and in the primary and middle French education schools. Finally, it is presented a series of philosophical and teaching arguments taken from Michel Tozzi’s work, as a condition that makes possible a teaching of the learning of philosophizing based on the range of theoretical and applied researches, field work, and the new practices of philosophizing teaching and philosophy itself in a changing social framework that generates challenges to the teaching of this discipline.